Foot orthoses for people with rheumatoid arthritis, involving quantitative and qualitative outcomes: protocol for a randomised controlled trial - Gabriel Gijon-Nogueron; Ana Belen Ortega-Avila; Laura Ramos-Petersen; Christoper J Nester (BMJ Open)
Introduction Rheumatoid arthritis (RA) involves changes to foot structure and function, and there is an association between RA and foot pain. This pain affects those patient’s physical activity and experience of daily living. While there is clinical evidence for the value of foot orthoses (FO) on foot pain, there is a wide range of FO available and there is little evidence on the relative benefits of one orthoses type over another, especially in terms of their impact on physical activity and associated well-being. The aim of this study is to compare physical activity, general and foot health and foot health experiences in people with RA when wearing three different types of FO.Methods and analysis A randomised controlled trial with three arms will compare the effects of (1) custom FO made using a direct adaptation technique, (2) custom FO made through a digital design and production process and (3) prefabricated orthoses. The primary outcome is physical activity measured using a GENEActiv bracelet. Secondary outcomes will be pain, function and disability and associated foot and general health evaluated using existing questionnaires. Semistructured interviews will identify patients’ experiences of the orthoses and living with RA.Ethics and dissemination The study has been approved by the Portal de Ética de la Investigación Biomédica de Andalucía ethical committee (SPAR-001). The results will be disseminated regardless of the magnitude or direction of effect.Trial registration number NCT03170947; Pre-results.